Research on Shape Changes in Cylinder Electrodes Incident to Micro-EDM - Xiaopeng Li; Yuangang Wang; Yu Liu; Fuling Zhao (Advances in Materials Science and Engineering)
This paper discusses electrode wear changes under different operating conditions. A series of experiments were designed and conducted using an EDM machine tool with a rectangular pulse power supply. The phenomena of the cylinder electrode shape changes were abstracted from the experiments; the change mechanisms of the end face are discussed and verified by experimental data and interrelated theory. The results disclose that the shape of an electrode is subject to pulse-on time, discharge current density, and electrode polarity.